Role Of Mass Media In Special Education (Journal of Namibian Studies : History Politics Culture, 2023)
The phrase "mass media" describes technology that is made for a big audience which includes printed publications like magazines, journals, newspaper, electronic media like television, radio and most importantly the internet. In the current study, the researchers look at the impact that mass media have in teaching the public, especially in terms of special education. Secondary data from different sources like newspaper article, journals, magazines are collected for the current study. And from the analysis of the provided information and the data we have found that media has a big influence on how we learn. The media has the power to influence our perception of ourselves, others, and our immediate environment. This study also conclude that the media has a big impact on how special needs kids are educated, even though it is insufficient. It covers everything, from their social to academic growth.